Pemanfaatan Protein pada Ayam Broiler yang Diberi Ransum Mengandung Kulit Pisang Fermentasi - Nur Adiva R. Situmorang; Bambang Sukamto; Edjeng Suprijatna (Composite : Jurnal Ilmu Pertanian, 2020)
The study was conducted from January to February 2014 in the Broiler Cage Stage Cikandang Village, Rumpin District, Bogor Regency, West Java. The study aims to examine the utilization of fermented banana peels on protein consumption, crude protein digestibility and protein mass of broiler chicken meat. The material used was 120 broiler chickens (unsex) with an average body weight of 475 ± 0.98 g / head for 14 days, rumen fluid, banana peels and rations arranged in iso energy and iso protein. The experimental design used was a completely randomized design (CRD) with 4 treatments and 6 replications. T0 treatment = control ration without banana peel; T1 = ration with 5% fermented banana peel; T2 = ration with 10% fermented banana peel; T3 = ration with 15% fermented banana peel. Banana peels are fermented for 1 week to reduce high fiber content and high tannin. Data were analyzed using the F test at a level of 5%, followed by the Duncan test if there is a treatment effect. Based on research results, protein consumption was not significantly different (P> 0.05), so was protein digestibility and protein mass. The conclusion of this study is the use of banana peels fermented with rumen fluid has not been able to increase protein digestibility, protein consumption and protein mass of broiler chicken meat. However, the use of banana peels to a level of 15% does not reduce the utilization of protein so that it can be used up to a mixture of broiler chicken rations. Suggestion from research is that further research needs to be done with a different starter or fermenter. Keywords: Broiler, banana peel, rumen fluid, protein utilization